Cognitive training improves executive function and self-efficacy in young women with chronic stroke: a pilot study - Scheffler, Michelle S.; Vas, Asha K.; Hay, Catherine Cooper; Griggs-Stapleton, Lisa; Cook, Lori G. (Frontiers in Human Neuroscience, 2025)
IntroductionYoung women are increasingly affected by stroke and often experience persistent executive function deficits that impact global functioning. The purpose of this pilot study was to evaluate the feasibility and effectiveness of a strategy-based cognitive training program (Strategic Memory Advanced Reasoning Training) to improve executive function and related outcomes in young women with stroke.MethodsEight women with chronic-stage stroke (age: M = 38.75 years; SD = ± 8.78) and eight age- and education-matched controls (age: M = 35.75 years; SD ± 7.71) completed 10 sessions of SMART over 5 weeks, with pre- and post- training assessments. Outcomes included measures of executive function (subtests of the BrainHealth Index), daily living skills (Cognitive Self-Efficacy Questionnaire, Daily Living Questionnaire, and Community Integration Questionnaire), and psychosocial functioning (Depression, Anxiety, and Stress Scale-21), as well as feasibility/goodness of fit of the program (Acceptability of Intervention Measure, Intervention Appropriateness Measure, and Feasibility of Intervention Measure).ResultsFollowing SMART, participants with stroke demonstrated improvements in aspects of executive function (including abstraction, strategic memory, and fluency of ideas), cognitive self-efficacy, and stress. Control participants also demonstrated gains, particularly in cognitive self-efficacy. Feasibility was rated highly by participants with stroke.DiscussionFindings support SMART as a promising intervention for enhancing cognitive and functional outcomes in young women with stroke, warranting further large-scale investigation.